Control and monitoring of solar photovoltaic panel using PLC - Mohd Jamil, Johanis (2013)
A renewable energy source plays an important role in electricity generation. Various renewable energy sources like wind, solar, geothermal, ocean thermal, and biomass can be used for generation of electricity and for meeting our daily energy needs. Energy from the sun is the best option for electricity generation as it is available everywhere and is free to harness. On an average the sunshine hour in Malaysia is about eight hours annually also the sun shine shines in Malaysia for about nine months in a year. Electricity from the sun can be generated through the solar photovoltaic modules (SPV). The SPV comes in various power output to meet the load requirement. Maximization of power from a solar photo voltaic module (SPV) is of special interest as the efficiency of the SPV module is very low. A peak power tracker is used for extracting the maximum power from the SPV module. The present work describes the potential system benefits of simple tracking solar system using stepper motor and light sensor. This method increases power collection efficiency by developing a device that tracks the sun to keep the panel at the right angle to its rays. A solar tracking system is designed, implemented and experimentally tested. The design details and the experimental results are shown.